GAMBARAN TINGKAT PENGETAHUAN IBU- IBU YANG MEMILIKI KEBIASAAN MEROKOK TENTANG KESEHATAN GIGI DAN MULUT TERHADAP OHI-S DI KELURAHAN TANAH MERAH KECAMATAN BINJAI SELATAN - Rosdiana Tiurlan Simaremare (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
Smoking habits can cause poor dental and oral. The knowledge of the mothers about oral and dental health is in low level, it is proven by the poor awareness of the mothers in maintaining their oral and dental hygiene. This study is descriptive research and it is to find out the description of the knowledge level of the mothers having smoking habit about dental and mouth health toward OHI-S in Tanah Merah, South Binjai sub-district. This study is conducted in survey method where the number of the samples is 25 people. The result of the research showed the knowledge level of the smoking mothers about dental and mouth health toward OHI-S in Tanah Merah, South Binjai sub –district that is as follow : 9 people (36%) are in good category, 16 people (64 %) are in moderate category and the OHI-S average is 3.4 which is in poor criteria. The conclusion of this research is that the knowledge level of the smoking mothers is in medium category, but the action of maintaining the dental and mouth hygiene is in poor category.